Negative pressure dressings are no better than standard dressings for open fractures. (13th March 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: Effect of negative pressure wound therapy vs standard wound management on 12-month disability among adults with severe open fracture of the lower limb: the WOLLF randomised clinical trial. Costa ML, Achten J, Bruce J, et al; UK WOLLF Collaboration Published on 9 October 2018 JAMA 2018;319:2280-8. This project was funded by the National Institute for Health Research Health Technology Assessment Programme (project number 10/57/20). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000655/negative-pressure-dressings-are-no-better-than-standard-dressings-for-open-fractures